Antioxidative enzymes, phytochemicals and proximate components in jujube fruit (Ziziphus mauritiana L.) with respect to genotypes and harvest maturity - Zohaib Asghar; Muhammad Amin; Sami Ullah; Hamad Hassan; Umm-e Habiba; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Aiyub; Shafa Nayab; Ambreen Naz; et al. (Food Bioscience, 2024)

Biogeographical patterns of blood parasite lineage diversity in avian hosts from southern Melanesian islands - Farah Ishtiaq; Sonya M. Clegg; Albert B. Phillimore; Richard A. Black; Ian P. F. Owens; Ben C. Sheldon (Journal of Biogeography, 2010)
Aim (1) To describe the species–area relationships among communities of Plasmodium and Haemoproteus parasites in different island populations of the same host genus (Aves: Zosterops ). (2) To compare distance–decay relationships (turnover) between parasite communities and those with potential avian and dipteran hosts, which differ with respect to their movement and potential to disperse parasite species over large distances. Location Two archipelagos in the south‐west Pacific, Vanuatu and New Caledonia ( c . 250 km west of Vanuatu) and its Loyalty Islands, with samples collected from a total of 16 islands of varying sizes (328–16,648 km 2 ). Methods We characterized parasite diversity and distribution via polymerase chain reaction (PCR) from avian ( Zosterops ) blood samples. Bayesian methods were used to reconstruct the parasite phylogeny. In accordance with recent molecular evidence, we treat distinct mitochondrial DNA lineages as equivalent to species in this study. Path analysis and parasite lineage accumulation curves were used to assess the confounding effect of inadequate sampling on the estimation of parasite richness. Species–area and species–distance relationships were assessed using linear regression: distance–decay relationships were assessed using Mantel tests. Results Birds and mosquito species and Plasmodium lineages exhibited significant species–area relationships. However, Plasmodium lineages showed the weakest ‘species–area’ relationship; no relationship was found for Haemoproteus lineages. Avian species richness influenced parasite lineage richness more than mosquito species richness did. Within individual avian host species, the species–area relationship of parasites showed differing patterns. Path analysis indicated that sampling effort was unlikely to have a confounding effect on parasite richness. Distance from mainland (isolation effect) showed no effect on parasite richness. Community similarity decayed significantly with distance for avifauna, mosquito fauna and Plasmodium lineages but not for Haemoproteus lineages. Main conclusions Plasmodium lineages and mosquito species fit the power‐law model with steeper slopes than found for the avian hosts. The lack of species–distance relationship in parasites suggests that other factors, such as the competence of specific vectors and habitat features, may be more important than distance. The decay in similarity with distance suggests that the sampled Plasmodium lineages and their potential hosts were not randomly distributed, but rather exhibited spatially predictable patterns. We discuss these results in the context of the effects that parasite generality may have on distribution patterns.

Avian haematozoan parasites and their associations with mosquitoes across Southwest Pacific Islands - F. ISHTIAQ; L. GUILLAUMOT; S. M. CLEGG; A. B. PHILLIMORE; R. A. BLACK; I. P. F. OWENS; N. I. MUNDY; B. C. SHELDON (Molecular Ecology, 2008)
The degree to which haematozoan parasites can exploit a range of vectors and hosts has both ecological and evolutionary implications for their transmission and biogeography. Here we explore the extent to which closely related mosquito species share the same or closely related haematozoan parasites, and examine the overlap in parasite lineages with those isolated from avian hosts, Zosterops species, sampled across the same study sites. Mosquito samples were collected and analysed (14 species, n = 804) from four islands in Vanuatu and the main island of New Caledonia. Using polymerase chain reaction, 15.5% (14/90) of pooled mosquito (thoracic) samples showed positive amplifications. Subsequent phylogenetic analysis of the cytochrome b gene identified four genetically distinct Plasmodium and two Haemoproteus lineages from these samples, five of which were identical to parasite lineages ( n = 21) retrieved from the avian hosts. We found that three Plasmodium lineages differing by a maximum of 0.9% sequence divergence were recovered from different species and genera of mosquitoes and two Haemoproteus lineages differing by 4.6% sequence divergence were carried by 10 distantly related (11–21% divergent) mosquito species. These data suggest a lack of both cospeciation and invertebrate host conservatism. Without experimental demonstration of the transmission cycle, it is not possible to establish whether these mosquitoes are the biological vectors of isolated parasite lineages, reflecting a limitation of a purely polymerase chain reaction‐based approach. Nonetheless, our results raise the possibility of a new transmission pathway and highlight extensive invertebrate host shifts in an insular mosquito–parasite system.